2021
DOI: 10.1590/1677-5449.210098
|View full text |Cite
|
Sign up to set email alerts
|

O volume de fluxo e a velocidade de pico sistólico ao ultrassom vascular com Doppler intraoperatório como preditores de perviedade precoce na fístula arteriovenosa autógena para hemodiálise

Abstract: Resumo Contexto A insuficiência renal crônica é um problema de saúde pública mundial. A hemodiálise é a principal terapia renal substitutiva. As fístulas arteriovenosas (FAV) são uma possível escolha, mas apresentam altas taxas de falência. Objetivos Este estudo tem como objetivo avaliar a relação entre as variáveis hemodinâmicas ao ultrassom vascular com Doppler no intraoperatório e a perviedade precoce da FAV para hemodiálise. Métodos Tratou-se de um estudo prospectivo observacional. Os pacientes consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…While angiography has been considered the gold standard for evaluating AVF status, spectral Doppler offers some diagnostic advantages over angiography. 21,26 In this case-control study, spectral Doppler assessment revealed significantly a lower FV and higher RI in unhealthy AVFs compared to those that were healthy. Other study variables that were investigated did not show significant differences.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…While angiography has been considered the gold standard for evaluating AVF status, spectral Doppler offers some diagnostic advantages over angiography. 21,26 In this case-control study, spectral Doppler assessment revealed significantly a lower FV and higher RI in unhealthy AVFs compared to those that were healthy. Other study variables that were investigated did not show significant differences.…”
Section: Discussionmentioning
confidence: 57%
“…The results of spectral Doppler examinations of the carotid, femoral, and lower extremity arteries have positioned spectral Doppler as a noninvasive and highly accurate diagnostic method for analyzing superficial vessels. 16 21 Various studies have also explored the role of peak systolic velocity (PSV) or systolic velocity ratio in diagnosing significant stenosis within an AVF. 5,21 24…”
mentioning
confidence: 99%
See 3 more Smart Citations